The Approaches and Effectiveness of Internet as a Media of Da'wah: A Research on Islamic Websites - Hazrina Abdul Hamid (Universiti Sains Islam Malaysia, 2009)
This research is assembled to foresee how far does the technology of Internet especially website and web applications are to be used as one of the media and channel (wasilah) to spread the Islamic Da'wah. With careful and continuous observation for 4 months, 3 different websites had been used as survey and random research using Islamic University College of Malaysia students who not specific in Islamic Studies as subjects. This research is for the awareness especially younger generations on how important Information Technology is and how powerful and useful Internet as the tool for spreading divine matters of Islamic Da'wah. The outcome of this research shows that using Internet as an education portal is still not wisely and widely used. Overall, the purpose of Internet is highly important in the Islamic Da'wah.